Serious Games for education and training - Alessandro De Gloria; Francesco Bellotti; Riccardo Berta (Serious Games Society, 2014)
Serious Games (SGs) are gaining an ever increasing interest for education and traning. Exploiting the latest simulation and visualization technologies, SGs are able to contextualize the player's experience in challenging, realistic environments, supporting situated cognition. However, we still miss methods and tools for effectively and deeply infusing pedagogy and instruction inside digital games. After presenting an overview of the state of the art of the SG taxonomies, the paper introduces the pedagogical theories and models most relevant to SGs and their implications on SG design.  We also present a schema for a proper integration of games in education, supporting different goals in different steps of a formal education process. By analyzing a set of well-established SGs and formats, the paper presents the main mechanics and models that are being used in SG designs, with a particular focus on assessment, feedback and learning analytics. An overview of tools and models for SG design is also presented. Finally, based on the performed analysis, indications for future research in the field are provided.